Elaboration of Benzoxadiazepine and Benzotriazocine Scaffolds. Issue 19 (15th May 2020) - Saied, Tarak; Efrit, Mohamed L.; Fort, Yves; Comoy, Corinne
Abstract: The synthesis of fused heterocycles containing several heteroatoms such as benzoxadiazepine and benzotriazocine scaffolds is considered as a complicated task due to their complex and polyunsaturated structures. In this review, we report the different methods and strategies that have been considered over the last decades for their synthesis. Abstract : Due to the presence of two oxygen and one nitrogen atoms in the benzo‐fused ring, the benzoxadiazepines and the benzotriazocines are attractive targets in heterocyclic chemistry. Because the development of convenient synthesis of such sensitive species is considered as a complicated task and remains an exciting challenge, this mini‐review explores various known synthetic approaches for the ring closure of these 7‐ and the 8‐membered condensed heterocycles.